Altered post‐capillary and collecting venular reactivity in skeletal muscle with metabolic syndrome. (5th July 2017) - Lemaster, Kent A.; Farid, Zahra; Brock, Robert W.; Shrader, Carl D.; Goldman, Daniel; Jackson, Dwayne N.; Frisbee, Jefferson C.
Abstract : Key points: With the development of the metabolic syndrome, both post‐capillary and collecting venular dilator reactivity within the skeletal muscle of obese Zucker rats (OZR) is impaired. The impaired dilator reactivity in OZR reflects a loss in venular nitric oxide and PGI2 bioavailability, associated with the chronic elevation in oxidant stress. Additionally, with the impaired dilator responses, a modest increase in adrenergic constriction combined with an elevated thromboxane A2 production may contribute to impaired functional dilator and hyperaemic responses at the venular level. For the shift in skeletal muscle venular function with development of the metabolic syndrome, issues such as aggregate microvascular perfusion resistance, mass transport and exchange within with capillary networks, and fluid handling across the microcirculation are compelling avenues for future investigation. Abstract: While research into vascular outcomes of the metabolic syndrome has focused on arterial/arteriolar and capillary levels, investigation into venular function and how this impacts responses has received little attention. Using the in situ cremaster muscle of obese Zucker rats (OZR; with lean Zucker rats (LZR) as controls), we determined indices of venular function. At ∼17 weeks of age, skeletal muscle post‐capillary venular density was reduced by ∼20% in LZR vs . OZR, although there was no evidence of remodelling of the venular wall. Venular tone at ∼25 μm (post‐capillary) and ∼75 μm (collecting) diameter was elevated in OZR vs . LZR. Venular dilatation to acetylcholine was blunted in OZR vs . LZR due to increased oxidant stress‐based loss of nitric oxide bioavailability (post‐capillary) and increased α1 ‐ (and α2 ‐) mediated constrictor tone (collecting). Venular constrictor responses in OZR were comparable to LZR for most stimuli, although constriction to α1 ‐adrenoreceptor stimulation was elevated. In response to field stimulation of the cremaster muscle (0.5, 1, 3 Hz), venular dilator and hyperaemic responses to lower frequencies were blunted in OZR, but responses at 3 Hz were similar between strains. Venous production of TxA2 was higher in OZR than LZR and significantly higher than PGI2 production in either following arachidonic acid challenge. These results suggest that multi‐faceted alterations to skeletal muscle venular function in OZR may contribute to alterations in upstream capillary pressure profiles and the transcapillary exchange of solutes and water under conditions of metabolic syndrome. Key points: With the development of the metabolic syndrome, both post‐capillary and collecting venular dilator reactivity within the skeletal muscle of obese Zucker rats (OZR) is impaired. The impaired dilator reactivity in OZR reflects a loss in venular nitric oxide and PGI2 bioavailability, associated with the chronic elevation in oxidant stress. Additionally, with the impaired dilator responses, a modest increase in adrenergic constriction combined with an elevated thromboxane A2 production may contribute to impaired functional dilator and hyperaemic responses at the venular level. For the shift in skeletal muscle venular function with development of the metabolic syndrome, issues such as aggregate microvascular perfusion resistance, mass transport and exchange within with capillary networks, and fluid handling across the microcirculation are compelling avenues for future investigation.